Peeling of finite-length elastica on Winkler foundation until complete detachment. (1st December 2022) - Plaut, Raymond H.; Hwang, Dohgyu; Lee, Chanhong; Bartlett, Michael D.; Dillard, David A.
Highlights: Peeling of beam until complete detachment from substrate. Beam modeled as inextensible elastica. Adhesive layer modeled as Winkler foundation. Beam loaded by end vertical displacement or rotation. Abstract: Quasi-static peeling of a finite-length, flexible, horizontal beam (strip, thin film) from a horizontal substrate is considered. The displaced end of the beam is subjected to an upward deflection or to a rotation. The action of the adhesive is modeled as a Winkler foundation, and debonding is based on the common fracture mechanics approach. The behavior is examined from the application of loading to the initiation of peeling and then to complete detachment of the beam from the substrate. During at least a portion of the debonding process, the model corresponds to what traditionally has been considered a short beam on an elastic foundation. In the analysis, the beam is modeled as an elastica, so that bending is paramount and large displacements are allowed. The effects of the relative foundation stiffness to the beam bending stiffness, the work of adhesion, and the length, self-weight, extensibility, and initial unbonded length of the beam are investigated. In addition, experiments are conducted to complement the analysis.